An appraisal of the phylogenetic relationships of Hypoptopomatini cascudinhos with description of two new genera and three new species (Siluriformes: Loricariidae) - Delapieve,Maria Laura S. (2017)
ABSTRACT The discovery of three new taxa of Hypoptotopomatini with ambiguous generic assignment prompted a reanalysis of the phylogenetic relationships of the tribe. The analysis focused on a data matrix of 56 terminals and 107 morphological characters comprising the three new taxa, most species of Hypoptopoma and Otocinclus, and all other species of the tribe. The 162 maximally parsimonious trees of 382 steps, consistency index of 0.41, and retention index of 0.83 were then summarized in a strict consensus tree. The results confirm the monophyly of the Hypoptopomatini, recover four genera as monophyletic (Acestridium, Hypoptopoma, Niobichthys, and Otocinclus), revealed Hypoptopoma and Oxyropsis to be non-monophyletic; and revealed two new genera within Hypoptopomatini. Additionally, Otocinclus was found to be sister to a group with all remaining genera of the tribe; Acestridium and Niobichthys were found to be sister to each other and that clade sister to a group formed by ((Leptotocinclus + Hypoptopoma [part]) + (Nannoxyropsis (Oxyropsis + Hypoptopoma [part]))). Based on this framework, changes to the classification and the taxonomy of the Hypoptopomatini are suggested and the new taxa are described.